BioNET goes global - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
BioNET INTERNATIONAL, an initiative which will help to create and sustain realistic, self-reliant plant and animal identification services throughout the developing world, has held its first Global Workshop. The meeting was held in the Welsh city of Cardi